(untitled) (Asian Business Research, 2018)
Cash flow is considered to be the main acceleration’s factor of any construction contract, which has a large and direct impact on projects completion dates as well as the project contractual duration. This is very evident when examining how the owners benefit from their projects in achieving or forfeiting the desired economic feasibility determined in the feasibility study of any project. It is noted that the cash flow plan is issued through a Critical Path Method (CPM) for a project which entails only an estimate of the monetary value of the construction work to be carried out on site and on a rough and approximate basis using the cash flow’s curve (S-CURVE), which is usually gives a different value from the actual work performed onsite. The impact of this problem on financial management for any project is as follows: In the case of underestimation, if the available estimates are less than the required cash flow, it is considered as a major cause for delay in project completion as well as the inability of the owner to achieve the economic feasibility Internal Rate of Return (IRR) required for the project. Also, this leads to monitory error due to the financial compensations due to the contractor as a result of the damage caused by time extensions due to the holdings of the cash entitlements. In the case of overestimation of the value of the required cash flow with a high margin of error, this leads to the monetary waste of amounts that could have been invested in other ventures, projects or opportunities. This paper provides a summary of the importance of determining the appropriate amount of cash flows required to be provided by the owner’s financial management, which leads to achieving the appropriate projects financial management gains and thus reducing financial losses or disputes in construction projects in the State of Kuwait.